2019
DOI: 10.1056/nejmoa1814630
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban for Thromboprophylaxis in High-Risk Ambulatory Patients with Cancer

Abstract: BACKGROUNDAmbulatory patients receiving systemic cancer therapy are at varying risk for venous thromboembolism. However, the benefit of thromboprophylaxis in these patients is uncertain. METHODSIn this double-blind, randomized trial involving high-risk ambulatory patients with cancer (Khorana score of ≥2, on a scale from 0 to 6, with higher scores indicating a higher risk of venous thromboembolism), we randomly assigned patients without deep-vein thrombosis at screening to receive rivaroxaban (at a dose of 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
611
2
23

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 580 publications
(651 citation statements)
references
References 28 publications
15
611
2
23
Order By: Relevance
“…The RCT compared 291 patients assigned to apixaban 2.5 mg twice daily vs 283 patients on placebo and reported symptomatic or incidental VTE outcome at 6 months. The CASSINI trial (international including the United States) enrolled adult patients with active cancer who were initiating new systemic therapy and had a Khorana score of 2 or higher . The median age was 63, and 51% were male.…”
Section: Resultsmentioning
confidence: 99%
“…The RCT compared 291 patients assigned to apixaban 2.5 mg twice daily vs 283 patients on placebo and reported symptomatic or incidental VTE outcome at 6 months. The CASSINI trial (international including the United States) enrolled adult patients with active cancer who were initiating new systemic therapy and had a Khorana score of 2 or higher . The median age was 63, and 51% were male.…”
Section: Resultsmentioning
confidence: 99%
“…Over time, VTE risk assessment at baseline may become less relevant for patients, but assessing dynamic risk factors such as hospitalization (demonstrated here), chemotherapy choice, or performance status may become more important. Two randomized trials were recently published using the Khorana score to risk stratify cancer patients for pharmacologic thromboprophylaxis . These trials demonstrated a modest benefit in VTE reduction at the expense of increased bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…DOACs have the advantage of oral administration without requiring intense laboratory monitoring. Apixaban for the Prevention of Venous Thromboembolism in High‐Risk Ambulatory Cancer Patients (AVERT) and CASSINI studies evaluated their benefit for primary VTE prophylaxis in intermediate to high‐risk ambulatory cancer patients …”
Section: Introductionmentioning
confidence: 99%
“…Both studies incorporated the Khorana score to target intermediate to high‐risk patients. AVERT used apixaban, whereas CASSINI used rivaroxaban for thromboprophylaxis …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation